Protective effect of Canna indica on cerebral ischemia-reperfusion injury in rats - Talluri, Mallikarjuna Rao; Killari, Kishore Naidu; Manepalli, N.V.S. Viswanadha Murthy; Konduri, Prasad; Bandaru, Kiran Kumar (Agriculture and Natural Resources, 2017)
The antioxidant capacity and cerebroprotective effect of Canna indica roots were estimated. The methanolic extract of C. indica roots was studied for free radical scavenging activity on superoxide, hydroxyl and 1, 1-diphenyl-2-picrylhydrazylfree radicals and compared with standard drug ascorbic acid using a pre-treatment for 1 wk at a daily oral dose, of 400 mg/kg or 800 mg/kg and then cerebral ischemiareperfusion injury was induced by occluding bilateral common carotid arteries for 30 min, followed by 4 h reperfusion. Quercetin (20 mg/kg, by intraperitoneal injection) was used as the standard drug. At the end of the experiment, animals were sacrificed by decapitation, and the brain was removed for the estimation of various biochemical parameters-assessment of cerebral infarct size and examination of oxidative stress enzymes such as superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA) and myeloperoxidase (MPO). Pre-treatment with methanolic extract of C. indica significantly reversed the levels of biochemical parameters and significantly reduced theedema and cerebral infarct size compared to the ischemic control group. The results indicated that C. indica ameliorates the cerebral ischemia/reperfusion injury and enhances the antioxidant defense. Further studies should involve the complete isolation of pure, biologically active compounds from the different extracts from C. indica like methanol in the present research.